The Extraction of Organic Silica from Agricultural Waste: A Mini Review - Zawati Harun,; Faiz Hafeez Azhar,; Rosniza Hussin,; Siti Aida Ibrahim,; Siti Khadijah Hubadillah,; Norsuhailizah Sazali, (Emerging Advances in Integrated Technology, 2024)
Inorganic silica precursors, also known as alkoxysilanes, have been used commercially in many applications and synthetizations. However, it has been reported that these inorganic silicas can harm human health, causing stomach, bladder, and kidney failure, as well as death in the case of an acute inhalation. Due to this reason, organic silica from agricultural waste such as coconut husks, corncobs, sugarcane bagasse, rice husks, and bamboo leaves is being reviewed as an alternative source to replace the risky inorganic silica. This work discussed the extraction method, silica percentage obtained, and applications involving the use of organic silica, demonstrating that green waste can replace inorganic silica and provide good value to society. Inorganic silica precursors, also known as alkoxysilanes, have been used commercially in many applications and synthetizations. However, it has been reported that these inorganic silicas can harm human health, causing stomach, bladder, and kidney failure, as well as death in the case of an acute inhalation. Due to this reason, organic silica from agricultural waste such as coconut husks, corncobs, sugarcane bagasse, rice husks, and bamboo leaves is being reviewed as an alternative source to replace the risky inorganic silica. This work discussed the extraction method, silica percentage obtained, and applications involving the use of organic silica, demonstrating that green waste can replace inorganic silica and provide good value to society.